Effect of detergent biodegradable (Aquil Sulfonate Sodium) oxygen consumption rate and filtration bivalve Semimytilus algosus - Alvarez, Guillermo (1999)
The specific (COE) and individual (COI) oxygen consumption of Semimytilus algosus (0,0856 to 0,1869 g) were determinated in static closed chambers.(300 ml aprox.), using 3 concentrations of detergent (CO = 0,00; C1 = 0,02; C2 = 0,04; and C3 = 0,06 mg I-1 of detergent). To detect the dissolved oxygen was used the Winkler method. The filtration rate was determinated without detergent by filtration of Chaetoceros gracifis, with the same individuals as were exposed to the detergent during the respiration experiments. The experiment conditions were 35%. of salinity and 17 ± 0,5ºC. The results indicated that the detergent, even though it is biodegradable, at short periods of exposition disturbs the respiration rate increasing the oxygen consumption and velocity of filtration rate with the increase of detergent concentration.